Moroccan fisheries policies (1956–72): the development of a foreign policy tool. - Torres-Garcia, Ana (Journal of North African Studies, 2025)
After gaining independence in 1956, the Moroccan government faced the challenge of boosting its economic development, which transformed the exploitation of its natural resources into a critical issue. However, reaching the government's aims was complicated by a number of different obstacles. Firstly, the government at the time was weak after the power struggle between the monarchy and the political parties from the nationalist movement, which were applying pressure to recover the territorial integrity of Morocco championed by Allal al-Fasi. Secondly, the country's weak economy, burdened by its colonial legacy, lacked financing capacity. Finally, territorial claims were causing problems with neighbouring countries, particularly Spain and Algeria. This study analyses Moroccan policy towards the fisheries sector and its gradual involvement under the foreign policy implemented by King Hassan II with regard to Spain and the claims to Western Sahara that began in 1956 and continued until the first Spanish-Moroccan fisheries treaty was abrogated in 1972. Drawing on French and Spanish diplomatic documents and newspaper sources, this work explains the interaction between internal and external factors in the evolution of the Moroccan policies regarding the fisheries question. The article analyses the details of the process in order to discover what elements played a role in the development of Moroccan fisheries policies and determine its place in the origins of the Western Sahara conflict.